2009
DOI: 10.1016/j.ajog.2008.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Obstetricians' choice of cesarean delivery in ambiguous cases: is it influenced by risk attitude or fear of complaints and litigation?

Abstract: Obstetricians' judgments about cesarean request in ambiguous clinical cases vary considerably. Perceived risk of complaints and litigation is associated with compliance with the requested cesarean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 112 publications
3
84
1
4
Order By: Relevance
“…The obstetrician will rarely be blamed for doing a cesarean section, while may be sued for not having done it. 8 In present study out of total 16% patients underwent VBAC, which is much higher than VBAC rates of 8.5 percent according to Hamilton BE et al 9 In present study 52.17% of patients had a successful VBAC, which is lower than that in other studies Landon and associates reported a success rate for vaginal delivery of 73.41% and Gonen et al reported a success rate of 79.66%. 4,10 Cowen and colleagues reported a successful VBAC of 81%.…”
Section: Discussioncontrasting
confidence: 53%
“…The obstetrician will rarely be blamed for doing a cesarean section, while may be sued for not having done it. 8 In present study out of total 16% patients underwent VBAC, which is much higher than VBAC rates of 8.5 percent according to Hamilton BE et al 9 In present study 52.17% of patients had a successful VBAC, which is lower than that in other studies Landon and associates reported a success rate for vaginal delivery of 73.41% and Gonen et al reported a success rate of 79.66%. 4,10 Cowen and colleagues reported a successful VBAC of 81%.…”
Section: Discussioncontrasting
confidence: 53%
“…I disse tilfellene kan man ikke utelukke at årsakene til keisersnittet var mer komplekse, og man kan derfor komme til å overvurdere kvinnens innflytelse (13,15). Studier fra Norge og andre europeiske land viser at en stor andel av obstetrikerne oppgir at deres praksis er påvirket av frykt for rettsforfølgelse (17,18). Dette kan vaere med på å drive keisersnittsfrekvensen oppover.…”
Section: Ikke-medisinskeunclassified
“…Several contributing factors from both the health provider and user sides have been identified, including fear of labour pain, misconceptions about vaginal delivery, previous traumatic births, social values, personal preferences, fear of litigation, economic reasons, and convenience for both patients and doctors. [8][9][10][11] An estimated 4-18% of all caesarean sections are performed exclusively as a result of maternal request. health costs, without evident health benefits; [13][14][15][16][17][18] however, many pregnant women do not receive clear information about these risks from their health providers.…”
Section: Introductionmentioning
confidence: 99%